The great fire of Rome : the fall of the emperor Nero and his city - Dando-Collins, Stephen (Da Capo Press, 2010)
On the night of July 19, AD 64, a fire began beneath the stands of Rome's great stadium, the Circus Maximus. For more than a week the fire spread, engulfing most of the city and nearly burning it to the ground. With its capital in ruins, Rome's powerful empire teetered on the edge of collapse as Nero struggled desperately to save his empire, and his skin. Historian Stephen Dando-Collins takes readers through the streets of ancient Rome, where unrest simmers, and into the imperial palace, where political intrigue seethes, relating a potboiler story filled with fascinating historical characters who will determine the course of an empire. It is an unforgettable human drama that brings ancient Rome and the momentous events of 64 AD scorchingly to life.--From publisher description.